VERIFIKASI MODEL KONDENSASI PADA RELAP5/SCDAPSIM/MOD 3.4 - Widodo, Surip (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
RELAP5/SCDAPSIM/MOD3.4 is one of computer programs that is often used for performing nuclear reactor safety system analysis. In order to know the accuracy of this computer program in predicting condensation heat transfer coefficient of vapor mixed with non-condensable gas, it is necessary to perform verification of the condensation model in the computer program. The verification is done by comparing prediction of condensation heat transfer coefficient value of RELAP5/SCDAPSIM/MOD3.4 with condensation heat transfer coefficient value of experiment result.. The comparison was done by performing simulation PCCS experiment facility into RELAP5 input model. The verification results indicate that RELAP5’s condensation model predicts lower condensation heat transfer coefficient by 20 % compared to the experiment result although has the same tendency. Therefore, a new better condensation correlation is needed to be applied in the RELAP5/SCDAPSIM/MOD3.4 to improve the heat transfer coefficient value of vapor with noncondensable gases.